KEMAMPUAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SMP AL MINHAJ TAMANSARI KECAMATAN TAMANSARI KABUPATEN BOGOR TAHUN PELAJARAN 2023-2024 - SUKENDAR (UNISAN JURNAL, 2024)
Developing teacher professional competence is important in improving the quality of education in schools. School principals have an important role and responsibility in developing teachers’ professional competence. Steps that can be taken by school principals include developing a structured and sustainable professional development program, providing adequate support and facilities for teachers, and encouraging collaboration between teachers in schools. Research shows that developing teacher professional competence can improve teacher performance, student motivation, collaboration between teachers, quality of education, and teacher satisfaction. Therefore, developing teacher professional competence needs to be a priority for school principals in improving the quality of education in schools. This research aims to explore the ability of school principals to improve the professional competence of teachers at Al Minhaj Tamansari Middle School, Tamansari District, Bogor Regency. This research uses a theoretical approach by conducting a literature study or literature review of several relevant references regarding the ability of school principals in developing teacher professional competence. The research results show that school principals have an important role and responsibility in developing teachers’ professional competence through preparing structured and sustainable professional development programs, providing adequate support and facilities for teachers, and encouraging collaboration between teachers in schools. The implementation carried out by the principal has succeeded in improving teacher performance and the quality of education at Al Minhaj Tamansari Middle School, Tamansari District, Bogor Regency. Therefore, this research recommends that school principals continue to carry out efforts to develop teacher professional competence to improve the quality of education at Al Minhaj Tamansari Middle School, Tamansari District, Bogor Regency.